Identification of two evolutionarily conserved genes regulating processing of engulfed apoptotic cells - Kinchen, Jason M. (2010)
Engulfment of apoptotic cells occurs throughout life in multi-cellular organisms. Impaired apoptotic cell clearance (due to defective recognition/internalization or degradation) results in autoimmune disease1, 2. One fundamental challenge in understanding how defects in corpse removal translate into diseased states is the identification of critical players orchestrating the different stages of engulfment. Here, through genetic, cell biological and molecular studies in C. elegans and mammalian cells, we identify SAND-1 and its partner CCZ-1 as new players in corpse removal. In sand-1- and ccz-1 deficient worms, apoptotic cells are internalized and the phagosomes recruit the small GTPase RAB-5, but fail to progress to the subsequent RAB-7(+) stage. The mammalian orthologues of SAND-1, Mon1a and Mon1b, were similarly required for phagosome maturation. Mechanistically, Mon1 interacts with GTP-bound Rab5, identifying Mon1 as a novel Rab5 effector. Moreover, a Mon1:Ccz1 complex (but not either protein alone) could bind Rab7 and also influence Rab7 activation, suggesting Mon1:Ccz1 as an important link in progression from Rab5+ to Rab7+ stages of phagosome maturation. Collectively, these data identify SAND-1(Mon1), and CCZ-1(Ccz1) as critical and evolutionarily conserved players regulating the processing of ingested apoptotic cell copses.